Burnout syndrome: antecedents and consequences in auditing profession. (2015) - Beuren, Ilse Maria; Vaz, Patricia Villa Costa; Bescorovaine, Rosiele
This study analyses the mediating role of the burnout syndrome in the relationship between its antecedents and consequences in auditing profession. The burnout dimensions considered were emotional exhaustion, reduced feelings of personal accomplishment and depersonalisation; for antecedents, perceived workload (overload), role ambiguity and role conflict; and for consequences, job satisfaction, performance and turnover intentions. To this end, descriptive research was carried out from the application of a questionnaire, with questions based on the studies of Guthrie and Jones III (2012) and Shih, Jiang, Klein and Wang (2013), in a sample of independent auditors. For data analysis descriptive statistics and structural equation modelling (SEM) were used. The survey results show consistent evidence of connections between antecedents and consequences of burnout, considering the mediating role of the burnout trends, since five of the six hypotheses tested were confirmed.